Peningkatkan Pemahaman Konsep Matematika Siswa Melalui Model Pembelajaran Flipped Classroom untuk Siswa Kelas VIII SMP - Wahyuni, Nurul; Izzati, Nur; Liana, Metta (Edumatica : Jurnal Pendidikan Matematika, 2023)
This study aimed to find out the difference between class VIII students of SMP Negeri 2 Bintan who used the Flipped Classroom learning model and conventional learning. This quantitative study uses a Quasy Experiment research type with a non-equivalent control group design. The sampling technique uses cluster sampling. The research instruments included interview sheets, observation sheets, and a description of 5 questions. The questions were then tested for validity, reliability test, difficulty level test, and discrimination test. The prerequisite tests carried out were the normality and homogeneity tests, and then the data results were normally distributed, and the two groups were homogeneous. The results showed that students in the experimental class obtained an average increase in their understanding of mathematical concepts by 0.35, while students in the control class obtained an increase of 0.21. Test the hypothesis using an independent t-test with a sig. (2-tailed) value of 0.000. Because this test is a right-hand side test, the p-value = × 0.000 = 0, and it is known that 0 ≤ 0.05, so is accepted. It can be concluded from this study that the increased understanding of mathematical concepts of students who learn with the Flipped Classroom model is higher than students who learn with conventional learning. It can be concluded from this study that the increased understanding of mathematical concepts of students who learn with the Flipped Classroom model is higher than students who learn with conventional learning.